Narrative strategies of modern Ukrainian Protestantism - Stavroiani, Sergii (Skhid, 2016)
The article examines the narrative strategies of Ukrainian Protestants for new translations of stories about their own tradition and to create posttraditional discourse about a "new Reformation" of postmodern era. The features of a narrative interpretation of Ukrainian Protestant of their churches in the postmodern context is comprehensively investigated. It is noted that in a in circumstances of ineffective of traditional sermon is attempt recovery of Protestant churches by the way of "new Reformation". It is found that the main narrative of the modern Ukrainian Protestant theology is the narrative of liberation "Exodus from Egypt" (Soviet and imperial totalitarianism) to a state of personal and social freedom. It is proved that narrative ideal of "postpostmodern" is a kind of romanticism in Theology, by kinship with the ideals of radical orthodoxy of Western Protestantism and concepts of Russian religious philosophy. The specificity of narrative ideal of "postpostmodern" is to claim deconstruction of modern and postmodern by it’s alteration, but not fundamentalistic reconstructing of traditions. The emergence of theology of postpostmodern in Ukraine is caused by events of Maidan and the subsequent crisis and a response of Protestant theological environment to contemporary challenges.